MENAKSIR EKSPOR KOTA MEDAN: PERBANDINGAN PENDEKATAN PENGELUARAN DENGAN BASIS EKONOMI - elvis purba (Journal of Economic and Business, 2019)
The objectives of this study are: (1) to estimate the export of Medan City by using an economical basis analysis, (2) compare the export value of the results of with the export data of the Medan City Statistics Agency (BPS), (3) compare the regression model of the export data of the study results this with the BPS data regression model, and (4) comparing the merits of the two simple linear regression equation models got. Export data were analyzed with the help of SPSS software version 20 for 2001-2017. The results of the data analysis show that: (1) the export value of the results of the economical basis analysis is always greater than the BPS data export, (2) based on the t test, exports have a positive and significant effect on the GRDP of the City of Medan in the sense that if exports increase then the GRDP will increase with a larger share of added exports. (3) The correlation coefficient between exports and GRDP is high while the coefficient of determination is moderate. (4) the simple linear regression equation between exports and the Medan City GRDP results of the economic base analysis do not differ significantly from the simple linear regression equation BPS data, (5) based on the normality test, the export data calculated by BPS and this research data are classified as normal. Based on the coefficient of determination, it turns out there are still other variables that affect the Medan City GRDP. Therefore, further research can consider other variables, such as public consumption, investment, and others.